PENINGKATAN KEMAMPUAN BERBICARA MELALUI METODE SHOW AND TELL PADA SISWA KELAS V SDN 17 LIMBOTO KABUPATEN GORONTALO - Arvandi Humokor P; Fandi H Binggo; Abd. Hamid Isa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
Speaking skill is an essential oral communication competence that needs to be developed in elementary school because it supports students’ confidence, classroom participation, and ability to convey ideas clearly. This study aims to improve the speaking skills of fifth-grade students at SDN 17 Limboto, Gorontalo Regency, through the implementation of the Show and Tell method. This research used Classroom Action Research based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection. The research involved 21 fifth-grade students and was conducted in two cycles. Data were collected through observation, interviews, speaking performance tests, and documentation, and were analyzed using descriptive percentage analysis. The initial observation showed that only 28% of students achieved the expected speaking criteria. After the implementation of Cycle I, students’ speaking mastery improved gradually through object-based presentations, guided discussion, and repeated practice. In Cycle II, the percentage of students who achieved the speaking criteria increased to 80%, while classroom participation and confidence also improved. These findings indicate that the Show and Tell method provides meaningful opportunities for students to practice speaking, organize ideas, use appropriate vocabulary, and present information in front of peers. Therefore, Show and Tell can be considered an effective instructional method for improving elementary students’ speaking skills in Indonesian language learning.